2019
DOI: 10.3389/fbioe.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Titanium–Tissue Interface Reaction and Its Control With Surface Treatment

Abstract: Titanium (Ti) and its alloys are widely used for medical and dental implant devices—artificial joints, bone fixators, spinal fixators, dental implant, etc. —because they show excellent corrosion resistance and good hard-tissue compatibility (bone formation and bone bonding ability). Osseointegration is the first requirement of the interface structure between titanium and bone tissue. This concept of osseointegration was immediately spread to dental-materials researchers worldwide to show the advantages of tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(168 citation statements)
references
References 120 publications
2
162
0
4
Order By: Relevance
“…Titanium implants usually have their surfaces modified after their initial fabrication in order to ensure that oxidation is uniform and that any contamination is removed [29]. The resulting surfaces have improved biological characteristics, and promote the processes of cell adhesion and proliferation, both of which contribute to bone bonding [30,31].…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Titanium implants usually have their surfaces modified after their initial fabrication in order to ensure that oxidation is uniform and that any contamination is removed [29]. The resulting surfaces have improved biological characteristics, and promote the processes of cell adhesion and proliferation, both of which contribute to bone bonding [30,31].…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Titanium (Ti) and its alloys are used for devices requiring strength, elongation, and long-term bone bonding in orthopedics, cardiovascular medicine, dentistry, and other applications owing to their high corrosion resistance, specific strength, and tissue compatibility [ 1 ]. Compared with other metals, Ti has the unique property of osseointegration.…”
Section: Current Clinical Issues Related To Titanium (Ti)mentioning
confidence: 99%
“…Osseointegrated titanium implant is frequently used for rehabilitation of loss organs due different causes, mainly trauma or diseases. It has been shown that titanium has properties that stimulate its interaction with bone tissue [1,2], presenting mechanical characteristics that adequately support the physiological stimuli (loads) received when in masticatory function [3]. Moreover, titanium implants show a good degree of predictability and durability, which are demonstrated by clinical studies [4,5].…”
Section: Introductionmentioning
confidence: 99%